Improving tofu product quality through the integration of the Kano model and Quality Function Deployment (QFD) - Dinda Finandita Putri; Annisa Kesy Garside; Thomy Eko Saputro; Tyas Yuli Rosiani; Mohd Nabil Bin Muhtazaruddin (Universitas Sultan Ageng Tirtayasa, 2026)
Many MSMEs struggle with process variations and inconsistent quality in the highly competitive tofu manufacturing industry. Problems such as unpleasant odors, inconsistent cut sizes, and irregular textures damage customer satisfaction and affect market competitiveness. In light of this, the aim of this study is to provide a systematic framework for identifying and prioritizing high-risk quality attributes in tofu products, using the case study in an MSME. Hence, this research develops a holistic approach that integrates the Kano model and Quality Function Deployment (QFD) to translate customer requirements into measurable technical actions. A survey of 73 respondents to the study identified 12 product attributes, classified into must-be, one-dimensional, and attractive attributes. So, these attributes were inserted in the HoQ-related matrix from which eight technical responses were ranked as mentioned before: high-quality soybean selection, elimination of chemical preservatives, boiling temperature control, and use of food-grade packaging materials. This integration provides a quantitative and systemic basis for process standardization in artisanal food production. It helps MSMEs establish an overarching strategic direction towards product consistency and, subsequently, competitiveness through data-driven quality improvement strategies.